Production Performance of Different Broiler Breeds Under Different Housing Systems - Al-Bahouh , Mariam E.; Al-Nasser, Afaf Y.; Abdullah, Faten K.; Ragheb, Gehan; Mashaly, Magdy M. (International Journal of Poultry Science, 2012)
In today's broiler industry, different housing systems are used in broiler production. However, the most common one is raising broilers on the floor. Raising broilers in the cages is another type of broiler housing system, but yet it is not commonly used. Raising broilers in cage system has many advantages when compared to raising broilers on the floor. The first obvious advantage is the better utilization of space available and that is important especially when the lands are expensive. In addition, using cage to raise broilers provide better hygienic condition that could lead to improving the health and quality of broilers. However, it is not known whether or not different broiler breeds will behave similarly when are raised in cage versus floor. Therefore, the current study was conducted to compare the production performance as well as %carcass of broilers raised in the cage system with broilers raised on the floor. In addition the %fat and %protein of meat from broilers raised under the two housing systems were measured. Three broiler breeds were used in three separate experiments. These breeds were Indian River, Cobb500 and Ross. Data on body weight, feed consumption were measured at 1, 3 and 5 weeks of age. Feed efficiency, %mortality, %carcass were calculated. In addition the %protein and %fat of breasts and legs of different breeds under the two housing systems were measured. Our results indicate that raising broilers in cages could provide better production efficiency than raising broilers on the floor. Furthermore, our results show that %protein is higher in the breast than in leg meat, however, %fat was higher in the leg than in the breast meat. In conclusion, our experiments emphasis the importance and significancy of utilizing cages to raise broiler chicks.